Circus Amok: - Maria Carolina Vasconcelos Oliveira (Revista Brasileira de Estudos da Presença)
This article examines Circus Amok, a circus company founded in 1989 in New York City, the United States, and directed by Jennifer Miller, a key figure in the debate on circus and political engagement, particularly in discussions on gender. By investigating secondary sources, including analyses of video recordings of performances and an interview with Jennifer Miller, the article explores the poetics and sensibilities at play in Circus Amok’s creations. The discussion considers Amok as a circus that simultaneously operates within the logic of the spectacle of attractions (in line with the American show business tradition) and articulates a political discourse that challenges structures of power (aligning with the tradition of politically engaged theater). Furthermore, the company draws on formal references from traditional circus while incorporating contemporary artistic discourses and issues.